The role of slow-wave sleep rhythms in the cortical-hippocampal loop for memory consolidation. (April 2020) - Navarrete, Miguel; Valderrama, Mario; Lewis, Penelope A
Abstract : Memory consolidation during slow-wave sleep is supported by slow oscillations (SOs), spindles, and hippocampal ripples. Recent evidence in both rodents and humans has demonstrated that consolidation is mediated by a bidirectional hippocampal-cortical loop. Here, we discuss oscillatory mechanisms by which the interaction of these non-REM oscillations may provide an appropriate neural framework for both the TOP-DOWN and the BOTTOM-UP processes in this loop. We also discuss how non-REM oscillations promote cortical plasticity for new memories, while simultaneously downregulating the representations of information in hippocampal networks. Finally, we point out that not all individual instances of non-REM oscillations play a role in the consolidation process. Instead, the capacity of these rhythms to support memory is determined by a triple SO-spindle-ripple coupling provided by thalamocortical dynamics. Importantly, large, spatially synchronized SOs promote thalamic down-states and spindles, boosting the probability of this triple coupling.